Temporal pattern of microbial indicators of ready-to-eat rocket salads during shelf life - Maria De Giusti; Angelo G. Solimini; Alessia Cottarelli; Corrado De Vito; Caterina Aurigemma; Daniela Tufi; Ludovico Piccinato; Antonio Boccia; Lucia Marinelli (Istituto Superiore di Sanità, 2014)
INTRODUCTION: From 2001-2009 there have been numerous community alerts and notifications about the rocket salad produced in Italy and distributed in Europe. Our study describes the evolution of the microbial quality of ready to eat rocket salad during shelf life among three different Italian producers. MATERIAL AND METHODS: Total Mesophilic Count (TMC) and Escherichia coli (EC) count were measured in 248 samples. We used Wilcoxon test to compare the median values of TMC and EC counts and Kruskal Wallis test to compare the producers. RESULTS: The TMC and EC values differed among producers at the stages of raw material and in the finished product (Kruskall Wallis test, p < 0.05). The evolution of bacterial charges had significant differences among producers at expiration date (Wilcoxon test, p < 0.05). More than half of the samples (54.8%) exceed reference standard for TMC after 48 h from packaging. CONCLUSION: Differences among producers may linked to the different minimal processing technologies adopted after harvesting.